Analisis Kasus Gangguan Kepribadian Avoidant Personality Disorder pada Siswa di MTs Nurul Aman - Fadilah, Risydah; Rakipah, Rakipah; Sinaga, Rizka Nisa Aulia; Matondang, Rizki Habibi (YASIN, 2023)
Personality disorder is a mental illness that makes individuals experience mistakes about their own behavior patterns related to interpersonal relationships. This mistake will prevent individuals from adjusting to their internal and external demands. Individuals with this personality disorder feel isolated or unacknowledged by people who are believed to not love them. Types of personality disorders according to Cluster C where individuals with this personality disorder show excessively anxious or fearful behavior include avoidant, dependent, obsessive-compulsive personality disorders. MTs Nurul Aman student with a history of the case of R who has avoidant personality disorder caused by R short or unclear speech that makes him an individual of inferiority. The behavior change that can be made to help this client is to use the Cognitive Behavior Therapy (CBT) approach.